Opportunities and challenges of integrating genetics education about human diversity into public health nurses' responsibilities in Japan - Hiromi Goda; Hiromi Kawasaki; Yuko Masuoka; Natsu Kohama; Md Moshiur Rahman (BMC, 2019)
Abstract Background Many genetic tests are now available due to evolution by the Human Genome Project. However, the growing use of genetic testing and screening may not only lead to improvements in public health and health promotion, but also trigger grave ethical, legal, and societal concerns. The involvement of community healthcare providers is expected in the future because they have direct contact with the residents through their health programs. The aims of the current study were to clarify how public health nurses perceive the relationship between genetics and professional duties and to identify opportunities and challenges of integrating genetics education into their professional duties. Methods In 2017, data were collected through a focus group interview. Content related to the 'presence or absence of health consultation related to genetic issues as part of actual job duties' and 'training for handling genetic-related health consultations' was extracted. Entire sentences were coded and categorized based on similar semantic content. Results Public health nurses had difficulties in recognizing genetic issues in public health activities. In some cases, genetic contents were included in conversation and consultation with the general public. Through the professional education and experiences, public health nurses needed specialized education, post-graduation studies and mentoring about genetics. Conclusions Public health nurses whose professional duties do not directly relate to genetics were exposed to genetics-related episodes on a regular basis without their awareness. The provision of accurate information and knowledge related to genetics by public health nurses would also provide an opportunity for clients to be informed about their latent genetic risks. Hence, there is a need for practical resources, the establishment of collaboration networks, and the development of professional organizations for public health nurses.